Peran Hakim dalam Penerapan Restorative Justice berdasarkan PERMA Nomor 1 Tahun 2024 - Jasri Akadol, Nina Septiana; Aswandi, Aswandi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study examines the role of judges in implementing restorative justice based on Supreme Court Regulation (PERMA) No. 1 of 2024. The background of this research stems from the need more humanistic approach within the criminal justice system, particularly in handling minor offenses. The purpose of this study is to analyze the role of judges in the implementation of restorative justice and to identify the challenges encountered in its application. The study uses a normative-empirical method, collecting data through document analysis and interviews with judges at the Pontianak District Court. The results of the study show that judges have a central role not only as ratifiers of agreements but also as facilitators, supervisors of the penal mediation process, and assessors of the integrity of agreements. However, the implementation still faces obstacles such as limited understanding, lack of mediation skills, and inadequate supporting infrastructure. Therefore, continuous training and systemic improvements are needed to optimize the judge's role in achieving restorative justice.